A primer on legal reasoning - Gold, Michael Evan (Cornell University Press, 2018)
After years of teaching law courses to undergraduate, graduate, and law students, Michael Evan Gold has come to believe that the traditional way of teaching - analysis, explanation, and example - is superior to the Socratic Method for students at the outset of their studies.In courses taught Socratically, even the most gifted students can struggle, and many others are lost in a fog for months. Gold offers a meta approach to teaching legal reasoning, bringing the process of argumentation to the fore.Using examples both from the law and from daily life, Gold's book will help undergraduates and first-year law students to understand legal discourse. The book analyzes and illustrates the principles of legal reasoning, such as logical deduction, analogies and distinctions, and application of law to fact, and even solves the mystery of how to spot an issue.In Gold's experience, students who understand the principles of analytical thinking are able to understand arguments, to evaluate and reply to them, and ultimately to construct sound arguments of their own.